Development and validation of a device for in vitro uniaxial cell substrate deformation with real-time strain control. (8th October 2020) - Apa, L; Carraro, S; Pisu, S; Peruzzi, B; Rizzuto, E; Prete, Z Del
Abstract: Substrate deformation affects the behaviour of many cell types, including bone, skeletal muscle and endothelial cells. Nowadays, in vitro tests are widely employed to study the mechanotransduction induced by substrate deformation. The aim of in vitro systems is to properly reproduce the mechanical stimuli sensed by the tissue in the cellular microenvironment. Accurate strain measurement and control is therefore necessary to ensure the cell senses the proper strain for the entire treatment. Different types of in vitro systems are commercially available or can be custom-designed; however, none of these devices performs a real-time measurement of the induced strains. In this study, we proposed a uniaxial strain device for in vitro cell stimulation with an innovative real-time strain control. The system was designed to induce sinusoidal waveform stimulation in a huge range of amplitude and frequency, to three silicone chambers stretched by a linear actuator. The real-time strain measurement and control algorithm is based on an optical tracking method implemented in LabVIEW 2015, and it is able to adapt the input amplitude to the linear motor, if necessary, hanging the stimulation signal for about 120 ms. Validation of the strain values measured during the real-time tracking algorithm was carried out through a comparison with the digital image correlation (DIC) technique. We investigated the influence of number of reference points and image size on the algorithm accuracy. Experimental results showed that the tracking algorithm allowed for a real-time measurement of membrane longitudinal strains with a relative error of 0.3%, on average, in comparison to the strains measured with DIC in post-processing analysis. We showed a high homogeneity of the strain pattern on the entire chamber base for different stimulation conditions. Finally, as proof of concept, we employed the uniaxial strain device to induce substrate deformation in a human osteosarcoma cell line (SaOS-2). The experimental results showed a consistent change in cell shape in response to the mechanical strain.